HAYWARD, Sarel Antoine Strydom Inventory of documents - HAYWARD, Sarel Antoine Strydom (ARCA, 2018)
Private papers of S.A.S. Hayward, National Party MP Graaff-Reinet [1969-1984], Deputy Minister of Agriculture [1978-1980], Agriculture and Fisheries [1980-1982], Minister of Environmental Affairs and Fisheries [1982-1984]
COVERAGE 3,44 Metres.
Keywords: HAYWARD, Sarel Antoine Strydom; Inventories; Politicians; National Party